Vibration isolation system with a compact damping system for power recycling mirrors of KAGRA. (12th April 2019) - Akiyama, Y; Akutsu, T; Ando, M; Arai, K; Arai, Y; Araki, S; Araya, A; Aritomi, N; Asada, H; Aso, Y; Bae, S; Baiotti, L; et al.
Abstract: A vibration isolation system called the Type-Bp system used for power recycling mirrors has been developed for KAGRA, the interferometric gravitational-wave observatory in Japan. A suspension of the Type-Bp system passively isolates an optic from seismic vibration using three main pendulum stages equipped with two vertical vibration isolation systems. A compact reaction mass around each of the main stages allows for achieving sufficient damping performance with a simple feedback as well as vibration isolation ratio. Three Type-Bp systems were installed in KAGRA, and were proved to satisfy the requirements on the damping performance, and also on estimated residual displacement of the optics.